The Spatial Variation of Lake Surface Water Temperature of Poyang Lake in Summer and Its Impact on Regional Precipitation - Miaoxia Tian; Haibo Zou; Jing Zheng; Anning Huang; Qi Huang (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2025)
With moderate resolution imaging spectroradiometer (MODIS) land surface temperature products, the spatial distribution of lake surface water temperature (LSWT) in Poyang Lake (PL) during summer are explored. Results show that the high-LSWT areas at noon [13:30 local solar time (LST)] are mainly located in the southwest, south, and east of PL where the water depth is relatively shallow, while the low-LSWT regions are situated in the middle and north of PL where the water depth is relatively deep, and the spatial difference can reach 1.5 °C. This distribution is obviously different from the previous finding (i.e., high LSWT in middle of north of PL, and low LSWT in southwest of PL). By night (01:30 LST), the distribution is roughly consistent with that at noon, rather than opposite. This is mainly induced by the relatively high air temperature over the PL region at night, which cannot only increase the downward longwave radiation of atmosphere, but also decrease the heat transport from lake to air, favorably reducing the heat loss in PL and slowing down the cooling of PL. To reveal the effects of the spatial variations of LSWT on regional precipitation, two sets of experiments, i.e., nonupdate experiment with default LSWT and update experiment with LSWT originated from MODIS data, are conducted, and results show that UP experiment obviously improves precipitation simulation in PL region. Diagnoses indicate that the effects of LSWT on local precipitation are accomplished through adjusting the low-level upward motion and atmospheric instability.